2013
DOI: 10.1161/strokeaha.112.673228
|View full text |Cite
|
Sign up to set email alerts
|

Intraventricular Fibrinolysis Does Not Increase Perihemorrhagic Edema After Intracerebral Hemorrhage

Abstract: PHE may play a role as a source of additional mass effect, especially in large ICH, and thereby lead to neurological Background and Purpose-Additional intraventricular hemorrhage leads to higher mortality and worse functional outcome after intracerebral hemorrhage (ICH). Intraventricular fibrinolysis (IVF) with recombinant tissue plasminogen activator (rtPA) is an emerging treatment strategy for such patients. However, experimental studies suggest that rtPA may exert proedematous effects and lead to increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 29 publications
(47 reference statements)
0
17
0
1
Order By: Relevance
“…Of the remaining 31 articles, 9 were excluded for the following reasons: 3 studies were excluded because they had no control group [20][21][22] and 6 studies were excluded because there was insufficient information for analysis. [23][24][25][26][27][28] One study identified through the previous meta-analysis was unpublished data and excluded from our analysis. Two additional studies were incorporated from a search of the reference lists of inclusion articles, resulting in 24 studies eligible for analysis ( Figure 1).…”
Section: Search Results and Included Articlesmentioning
confidence: 99%
“…Of the remaining 31 articles, 9 were excluded for the following reasons: 3 studies were excluded because they had no control group [20][21][22] and 6 studies were excluded because there was insufficient information for analysis. [23][24][25][26][27][28] One study identified through the previous meta-analysis was unpublished data and excluded from our analysis. Two additional studies were incorporated from a search of the reference lists of inclusion articles, resulting in 24 studies eligible for analysis ( Figure 1).…”
Section: Search Results and Included Articlesmentioning
confidence: 99%
“…Intraventricular fibrinolysis with rtPA was an emerging therapy for clearing IVH as soon as possible. It was shown to clear IVH without increasing perihaemorrhagic oedema 40. Recently, a large, phase III, multicentre, randomised, placebo controlled clinical trial evaluating the use of intraventricular tPA administration in patients with IVH has completed enrolment.…”
Section: Reversal Of Coagulopathiesmentioning
confidence: 99%
“…As a first identified receptor of thrombin, PAR1 is one of the most important PARs involved in neurotoxicity and neuronal apoptosis 31 32 . Studies showed that excess thrombin could induce neurotoxic effects and neuronal apoptosis via PAR1 activation 33 34 35 36 . Based on these lines of evidence, we speculated that thrombin directly activated PAR1 in the course of ICH, leading to the activation of a series of downstream signaling pathways that mediate ICH injuries.…”
Section: Discussionmentioning
confidence: 99%